Maternal and neonatal seroprevalence of Hepatitis B surface antigen (HBsAg) in Tripoli, Libya - Hamida El-Magrahe; Abdul Rahaman Furarah; Kheiria El-Figih; Sued El-Urshfany; Khalifa Sifaw Ghenghesh (Journal of Infection in Developing Countries)
Background: Pregnant women with Hepatitis B virus HBV represent a major reservoir of the virus in the community. Data regarding the prevalence of HBV in pregnant women and maternal transmission of the virus in Libya are lacking.